Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking